PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMP NEGERI 2 SUSUKAN LEBAK - Wawat Hermawati; Rohmatul Fawaiz; Laelatul Nurjanah (Jurnal Ekonomi Manajemen, 2021)
This study aims to determine the effect of principal transformational leadership on teacher performance at SMP Negeri 2 Susukanlebak. The type of research used in this study uses a quantitative approach with simple regression analysis techniques. The type of data used is primary data obtained through a questionnaire using SPSS for Windows version 18 and observation. Secondary data obtained from school data as well as several books and journals that can be accounted for. The sample in the study was 36 respondents using saturated sampling technique. The results of this study based on the value of R Square indicate that the principal's transformational leadership has a contribution of 20.1% or there is a low influence of 20.1% on teacher performance at SMP Negeri 2 Susukanlebak. The remaining 79.9% is influenced by other factors not examined by the authors.